Staphylococcus Aureus-Induced Myositis Of The Iliococcygeus Muscle - Suresh, Mandara Mathighatta; Siddappa, Usha Dhoddametikurke; Katchhi, Mohd Sharique; Aditya, Chakure; Basavaraju, Chinthana Handankere; Muralidhar, Shilpashree Bettadapura (Journal of Neonatal Surgery, 2025)
Objective : To describe the clinical presentation, diagnostic process, management, and outcome of a rare case of Staphylococcus aureus-induced myositis involving the iliococcygeus muscle in a young female patient, and to highlight the importance of early diagnosis and tailored antibiotic therapy in musculoskeletal infections. Materials and Methods : A single case report was conducted following Consensus-based clinical case reporting guidelines. Data were collected from a 29-year-old female presenting with left hip pain. Patient history, physical and laboratory examinations, and imaging studies (MRI) were documented. Laboratory investigations included complete blood count, C-reactive protein (CRP), blood cultures, and Xpert MTB/RIF Ultra testing. Empirical antibiotic therapy was initiated and subsequently adjusted based on culture sensitivity results. Clinical response was monitored through symptom resolution, inflammatory marker trends, and follow-up MRI scans. Ethical considerations, including informed patient consent and confidentiality, were maintained throughout the study. Results : The patient presented with progressive left hip pain. MRI revealed marked inflammatory changes and edema in the iliococcygeus, pectineus, and adductor longus muscles, with early abscess formation. Laboratory findings showed significantly elevated CRP and lymphocyte counts. Microbiological testing identified Staphylococcus aureus as the causative organism, resistant to several antibiotics but susceptible to oxacillin and vancomycin. Initial intravenous broad-spectrum antibiotics were administered, later switched to oral doxycycline and clindamycin based on sensitivity results. The patient completed a 15-day course of antibiotics, resulting in full clinical recovery and normalization of inflammatory markers. No complications were observed during follow-up. Conclusion : This case underscores the diagnostic challenges and therapeutic strategies in managing deep pelvic myositis due to Staphylococcus aureus. Early imaging, prompt microbiological assessment, and tailored antibiotic therapy were crucial for a favorable outcome. Clinicians should maintain a high index of suspicion for musculoskeletal infections in atypical presentations to enable timely intervention and prevent complications.